BIOLOGICALLY ACTIVE TRITERPENES FROM EUGENIA PISIFORMIS CAMBESS. (MYRTACEAE) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
In Brazil, Eugenia pisiformis, which belongs to botanical family Myrtaceae occurs in the states of Rio de Janeiro, Espírito Santo, Maranhão and Bahia. A specimen of E. pisiformis collected in Itatiaia National Park, State of Rio de Janeiro had its leaves, were studied because there are no phytochemical data in the literature for this plant so far. From the ethanolic extract of the leaves 3 substances were isolated and identified as the cycloartane-type triterpene 24-methylenepollinastanol, oleanane-type triterpene uvaol and ursane-type triterpene erythrodiol. All of them present significant biological properties, according to the literature and 24-methylenepollinastanol have never been isolated from this species, genus or family.